Is Inflation in Pakistan a Monetary Phenomenon? (The Pakistan Development Review, 2006)
The paper finds that an increase in money supply over the long-run results in a higher rate of inflation and thus provides support for the quantity theory of money. It establishes that inflation is essentially a monetary phenomenon. However, the money supply does not instantly influence the price levels; the impact of money supply on inflation has a considerable lag of about 9 months. While the study shows that the money supply works through the system in less than a year, it also points out that the system takes rather long to converge to equilibrium if shocks appear in any of the three variables, viz., GDP, money supply, and prices. JEL classification: N15, E31, E51 Keywords: Growth, Inflation, Money Supply, QTM